Three new species of Phyllocoptinae mites (Prostigmata: Eriophyidae) associated with ornamental plants in Brazil - Navia, Denise; Flechtmann, Carlos H.w. (Zootaxa, 2007)
Three new species of Phyllocoptinae mites (Prostigmata: Eriophyidae) from Brazil namely Acaricalus souzae n. sp. (Acaricalini), from common morning glory, Ipomoea purpurea (Convolvulaceae); Aculops fenestratus n. sp. (Anthocoptini), from royal poinciana or flamboyant, Delonix regia (Fabaceae); and Porcupinotus costaspinosus n. sp. (Anthocoptini), from Abarema cochliacarpos (Mimosaceae) are described. The eriophyoid mite species were causing no apparent damage.